2017
DOI: 10.18203/2394-6040.ijcmph20172865
|View full text |Cite
|
Sign up to set email alerts
|

An association of knowledge and misconceptions with health seeking behaviour for dog bite: a cross-sectional study in Ahmedabad

Abstract: Background: Rabies is a deadly zoonotic disease and most often transmitted to humans through a dog bite. It is 100% fatal yet 100% preventable with timely and appropriate Post Exposure treatment. There are myths associated with a dog bite and rabies and which might affect the health seeking behaviour. The objectives of the study were to assess the knowledge and misconceptions regarding dog-bite and rabies in primary school teachers and to know the association of misconceptions with health seeking behaviour for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Likewise, a study conducted by Ganasva et al, showed that 95.8% of the exposures were from stray dogs. 15 Similarly, a study conducted by S Sharma et al showed that, 84.2% of the exposures were on lower limbs. 14 A study by Trivedi et al, showed that 82.85% of bites were by dogs, 52.06% were by stray animals, 78.41% was unprovoked bites,62.59% of bites were over lower limbs, 70.74% suffered from multiple bites/scratches and 73.01% were category III bites.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Likewise, a study conducted by Ganasva et al, showed that 95.8% of the exposures were from stray dogs. 15 Similarly, a study conducted by S Sharma et al showed that, 84.2% of the exposures were on lower limbs. 14 A study by Trivedi et al, showed that 82.85% of bites were by dogs, 52.06% were by stray animals, 78.41% was unprovoked bites,62.59% of bites were over lower limbs, 70.74% suffered from multiple bites/scratches and 73.01% were category III bites.…”
Section: Discussionmentioning
confidence: 92%
“…14 Similarly, a study by Ganasva et al showed that 93.8% approached Government health care facilities for post exposure prophylaxis and 64.1% travelled <10kms to approach the health care facility. 15 A study by Anshuli Trivedi et al, showed that, 53.01% washed their wound with soap and water. 16 A study by Venkatesan et al, showed that only 36% washed their wounds with soap and water, 65% received treatment from primary health centre.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other rabies endemic countries have found similar or much higher proportion of rabies exposed victims (Sri Lanka: 7.3%, Tanzania: 20%, Guangdong province in China: 67% and Philippines: 92%) who did not seek PEP following potential rabies exposure from animal-bite [28–32]. Awareness level about rabies, socio-economic status, accessibility and availability of PEP are some of the major factors associated with PEP seeking behavior by the victims following potential rabies exposures [1, 3, 33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…During the In-Depth Discussion it was revealed that not all cases of dog bites were unprovoked. Lack of understanding of dog gestures, which could have led to unprovoked dog bites, were previously reported especially among children [ 29 , 40 , 41 ]. Therefore, reinforcing findings from the current study.…”
Section: Discussionmentioning
confidence: 99%